Child interaction: perspectives, activities and outcomes - Sakellariou, Maria, 1962- (Hauppauge,NY: Nova Science Publishers, 2021)
'Today, there is a growing scientific and research interest in the study of child interaction and its importance in development, learning and well-being. The research interest is fueled by a timeless documentation that children who come to kindergarten with a developed ability to interact with their peers, have more positive attitudes towards school, gain higher performance in cognitive subjects and adapt more quickly to new experiences. In fact, modern research shows that participation in high-quality education and training programs during childhood has a positive impact on academic achievements in school, reduces the risk of school repetition and reduces the need for intervention for social or special educational reasons. Child interaction and the acquisition of basic social skills begins early, from early childhood and is shaped over time, provided that children are given the opportunity to acquire them. In the context of these reflections on the importance of child interaction and wishing to contribute to the teaching and educational work of teachers and future teachers of preschool and school education, but also the family in the context of cooperation with the school, this book was written. The authors of this collective volume, with many years of personal experience, document with scientific validity of the importance of interaction in childhood, and their impact on children's lives'--
Children's interaction : theoretical considerations, research issues, challenges and perspectives / Maria Sakellariou -- Contribution of play in the interaction among pre-school age children : an example in a Greek kindergarten / Maria Sakellariou and Maria Banou -- Degrees of freedom in collective play : how different institutions create diverse conditions for young children's interactions / Glykeria Fragkiadaki, Marilyn Fleer and Prabhat Rai -- Social interactions for children on the autism spectrum : an exploration of parent, sibling, and peer relationships / Kathryn E. Parisi, Ayla R. Mapes, and Lauren B. Quetsch -- Enhancing interaction through the implementation of differentiated instruction in pre-school and school age : a case study / Maria Sakellariou, Polyxeni Mitsi and Panagiota Strati -- Educational cultural workshops for children aged 3-5 from diverse cultural backgrounds at early childhood education and care (ECEC) facilities : a framework of practice of the Erasmus+ 2018 Strategic Partnership Project EDUCLAB (Education and Digital Cultural Laboratory) / Loizos Symeou, Elena Stylianou, Chrystalla Papademetri, Sophia Hadjipapa and Georgia Petroudi -- The anatomy of teacher students' questioning and feedback image in Greek kindergarten classrooms and the effect of applied teaching approach / Efthymia Gourgiotou -- The contribution of primary school students' interaction with visual representations in additive problem solving / Iliada Elia -- Interaction and social relationships during the transition from kindergarten to elementary school : a case study in Greece / Maria Sakellariou, Panagiota Strati and Polyxeni Mitsi -- Grandparenting children with and without special educational needs : the role of familial interactions / Maria Kypriotaki and Ekaterina Kornilaki -- Using the dynamic model of educational effectiveness to identify stages of effective teaching and assessment / A. Dimosthenous and L. Kyriakides -- Diversity and child interactions in the early childhood curriculum of Ireland / Evanthia Synodi -- Beliefs and intentions of Greek educators on the role of play regarding interaction within pre-school and school eEnvironments / Maria Sakellariou and Maria Banou.
Includes bibliographical references and index.
Keywords: Social skills -- Study and teaching (Early childhood).; Social skills in children; Social interaction in children; Interpersonal relations in children; Child development